DOI: 10.18297/etd/1398
|View full text |Cite
|
Sign up to set email alerts
|

Improving screening for externalizing behavior problems in very young children : applications of item response theory to evaluate instruments in pediatric primary care.

Abstract: Studts, Christina Ruth 1971-, "Improving screening for externalizing behavior problems in very young children : applications of item response theory to evaluate instruments in pediatric primary care." (2008) My family has also been a constant source of encouragement and strength. My parents, Bob and Kathy Clark, instilled in me a love of learning, a passion to achieve, and a focus on concern for others. My sister and fellow lifelong student, Jeannie ClarkMabey, has shared in the joys of returning to school in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 211 publications
(345 reference statements)
0
7
0
Order By: Relevance
“…Prior studies had shown evidence of gender and race/urban status differences in conduct problems, but few studies had tested for DIF across gender and race/urban status (Gross et al, 2006; Studts, 2008). Our results indicated substantial DIF, both uniform and nonuniform across gender, but not across race/urban status.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies had shown evidence of gender and race/urban status differences in conduct problems, but few studies had tested for DIF across gender and race/urban status (Gross et al, 2006; Studts, 2008). Our results indicated substantial DIF, both uniform and nonuniform across gender, but not across race/urban status.…”
Section: Discussionmentioning
confidence: 99%
“…The BPI was created by Peterson and Zill (1986) to measure the frequency, range, and type of childhood emotional and behavioral problems. It has been shown to be associated with clinically significant psychosocial symptoms (Studts, 2008). It is a well-established index used in many major surveys such as the National Longitudinal Study of Youth and the Panel Study of Income Dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…We also compared the test information (Hambleton and Swaminathan 1985) curves among the subscales. The test information function is defined for a particular set of items (e.g., a subscale) at each point along with the continuum of the latent factor (Studts 2008). The contribution of each item to the total test information function is additive.…”
Section: Analysesmentioning
confidence: 99%